Estimating land surface temperature to study land use land cover influence on the temperature in a city with a dry arid climate. Issue 1 (1st July 2022) - Albakri, Naseeb Asaad; Al-Ruzouq, Rami; Shanableh, Abdallah; Zeiada, Waleed; Hamdan, Hamdan
Abstract: Turning arid regions or forests into urban areas (Urbanization) is affecting the global temperature. This effect is intensifying due to uncontrolled urban growth. To understand the influence of land use land cover (LULC) on land surface temperature (LST) in dry arid climate cities like Sharjah, UAE, 2 Landsat 8 images were used to retrieve the LST, one in summer and one in winter by using the radiation correction equation in google earth engine. Supervised classification of a high-resolution image from worldview-3 will produce the LULC map. In addition, hourly ground temperature data (GT) is retrieved from 6 field stations to validate LST and find the correlation if it exists. The LST images were then compared to the different LULC, to find relationships between the two. This study showed that barren soil experienced the highest LST when compared to vegetation and urban areas, and vegetation areas experienced the lowest temperatures compared to all other LULC, finally, urbanization that was combined with green lands can have a positive impact on the temperature in cities with dry arid climates. This study proves that understanding the effects of urbanization on temperature accurately will aid greatly in the future planning of cities.